2011
DOI: 10.3109/17435390.2011.606926
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle inhalation alters systemic arteriolar vasoreactivity through sympathetic and cyclooxygenase-mediated pathways

Abstract: The widespread increase in the production and use of nanomaterials has increased the potential for nanoparticle exposure; however, the biological effects of nanoparticle inhalation are poorly understood. Rats were exposed to nanosized titanium dioxide aerosols (10 µg lung burden); at 24 h post-exposure, the spinotrapezius muscle was prepared for intravital microscopy. Nanoparticle exposure did not alter perivascular nerve stimulation (PVNS)-induced arteriolar constriction under normal conditions; however, adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 61 publications
7
64
2
Order By: Relevance
“…29 Similar microvascular dysfunction has been reported after inhalation of nano-titanium dioxide and has been associated with stimulation of sensory neurons from the lung and enhanced sympathetic input at the systemic arterioles. 30,31 Aspiration of MWCNTs has also been reported to increase baroreflex activity in rats. 32,33 In addition, Erdely et al 34 reported transient elevation of blood inflammatory mediators after aspiration of MWCNTs, which may mediate this systemic microvascular response.…”
Section: Cardiovascular Responsesmentioning
confidence: 99%
“…29 Similar microvascular dysfunction has been reported after inhalation of nano-titanium dioxide and has been associated with stimulation of sensory neurons from the lung and enhanced sympathetic input at the systemic arterioles. 30,31 Aspiration of MWCNTs has also been reported to increase baroreflex activity in rats. 32,33 In addition, Erdely et al 34 reported transient elevation of blood inflammatory mediators after aspiration of MWCNTs, which may mediate this systemic microvascular response.…”
Section: Cardiovascular Responsesmentioning
confidence: 99%
“…Maintaining the appropriate environmental parameters inside the chamber is insufficient if the concentration of test compound varies from location to location 3 . The nanoparticle concentrations were measured at four different locations in the zones just above the cages in the exposure chamber.…”
Section: Uniformity Of Distributionmentioning
confidence: 99%
“…Whereas studies of neurological dysfunction impairing the resistance vasculature remain limited, our work has indicated that inhalation of titanium dioxide nanoparticles leads to a perturbation of physiologic alpha-adrenergic receptor sensitivity, inducing a persistent, sympathetically mediated arteriolar dysfunction (68). Because maintenance of systemic blood pressure is largely influenced by peripheral vascular resistance, the need to evaluate the resistance vasculature directly becomes evident.…”
Section: Cardiovascular Outcomesmentioning
confidence: 96%